Reproductive Plasticity in the Speckled Crab Arenaeus cribrarius (Decapoda, Brachyura, Portunidae) Associated with a Population Decline - Andrade, Luciana S. [UNESP]; Fransozo, Vivian [UNESP]; Bertini, Giovana [UNESP]; Negreiros-Fransozo, Maria L. [UNESP]; Lopez-Greco, Laura S. [UNESP] (Coastal Education &research Foundation, 2015)
Reproductive strategies are responsible for population maintenance, and when equilibrium is achieved, the selected strategy may become a pattern. The shaping of these patterns is an important resource for a species'conservation and should receive special attention. The population biology of Arenaeus cribrarius was evaluated, focusing on recruitment, sexual maturity, and reproductive period, and the results were compared with available information about this species from previous catches. Crabs were collected monthly for 3 years, and for each specimen the sex, gonadal development, breeding condition, and carapace width (CW) were recorded. Seawater temperatures (from bottom and surface) were also recorded. Reproduction and recruitment only occurred during the warmer months of the year, and size at sexual maturity was smaller (50.1 mm CW) in males than in females (56.3 mm CW). These features differed from previous studies of the same species in the same sampling area, suggesting the plasticity of the reproductive strategy to optimize reproductive success and survival of the larvae.
Keywords: Population regulation; sexual characters; sexual maturity; stock enhancement; reproductive strategy